2003
DOI: 10.1124/jpet.103.049916
|View full text |Cite
|
Sign up to set email alerts
|

Functional Melatonin Receptors in Rat Ovaries at Various Stages of the Estrous Cycle

Abstract: This study investigated the receptor mechanism(s) by which the hormone melatonin directly affects ovarian function. Expression of MT 1 and MT 2 melatonin receptor mRNA was detected in the rat ovaries both by reverse transcriptase-polymerase chain reaction and in situ hybridization with digoxigenin-labeled oligoprobes. Exposure of granulosa cells in culture to 17␤-estradiol seems to alter the state of melatonin receptor coupling. Indeed, the efficacy of 4P-PDOT on forskolin-stimulated cAMP formation was reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
125
0
11

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(139 citation statements)
references
References 40 publications
3
125
0
11
Order By: Relevance
“…This is consistent with the earlier reports on human and rat demonstrating the presence of MTNR1A and MTNR1B in granulosa cells and luteal cells (Soares et al 2003). The presence of high levels of melatonin in follicular fluid in human and binding sites in the ovary (Brzezinski et al 1987, Ronnberg et al 1990, Niles et al 1999 and, now, the presence of MTNR1A and MTNR1B in ovary suggest that melatonin directly acts as a modulator of ovarian functions.…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with the earlier reports on human and rat demonstrating the presence of MTNR1A and MTNR1B in granulosa cells and luteal cells (Soares et al 2003). The presence of high levels of melatonin in follicular fluid in human and binding sites in the ovary (Brzezinski et al 1987, Ronnberg et al 1990, Niles et al 1999 and, now, the presence of MTNR1A and MTNR1B in ovary suggest that melatonin directly acts as a modulator of ovarian functions.…”
Section: Discussionsupporting
confidence: 82%
“…Reported increases in prolificacy subsequent to the administration of melatonin in sheep might be due to the direct effect of exogenous melatonin on the ovine oocyte, which has been observed in other species (Ishizuka et al, 2000;Na et al, 2005;Parka et al, 2006). Several studies have reported the presence of melatonin in human pre-ovulatory follicular fluid and the seasonal variation of its contents (Brzezinski et al, 1987;Yie et al, 1995), and melatonin receptors have been found on rat, mouse, and porcine ovarian cells (Soares et al, 2003;Na et al, 2005;Kang et al, 2008), which suggests that melatonin has a direct effect on oocyte competence.…”
mentioning
confidence: 99%
“…Melatonin is found in ovarian follicular fluid (Rönnberg et al, 1990), suggesting a direct effect of this hormone on ovarian function. The effects of melatonin on ovarian function vary with tissue structure, cell type, and with the fact whether the species is a seasonal or non-seasonal breeder (Soares et al, 2003). Two high-affinity melatonin receptor types, MTNR1A and MTNR1B, have been cloned in humans, sheep, Siberian hamsters, mice, and rats (Nishiyama et al, 2009) and found to exhibit different molecular structures and chromosomal locations among these species.…”
mentioning
confidence: 99%